Bio-based multilayer paperboard for sustainable packaging application - Santos, Jackson Wesley Silva dos (2023)
Bio-based packaging materials are an emerging environment-friendly alternative to conventional plastic food packaging materials, at least for some applications. The innovation of this work was to develop a sustainable cellulosic packaging material based on chitosan/palmitic acid/activated carbon coating with potential applications for single-use food packaging. The study developed a multilayer paperboard (MPB), evaluating the effects of a paperboard surface coating by chitosan (2.0% w/w), palmitic acid (1.8% w/w), and activated carbon (1.2% w/w) applied in three coating layers. The water vapor transmission rate (WVTR) of coated paperboard was reduced compared to uncoated paperboard, associated with the coating suspension filling of the pores of the cellulosic matrix, the palmitic acid hydrophobic characteristic, and the nonpolar nature of activated carbon (acted by repelling the vapor molecules of water). A grease resistance of Kit solution 11 of MPB was observed. The stiffness and elongation capacity increased, indicating the rigidity and flexibility of the MPB. The deposition of palmitic acid and activated carbon influenced the roughness increase. The biodegradability in the soil after 188 days of MPB was 55.01%, and the control (uncoated paperboard) was 69.38%. The coating did not impact the degradation behavior of cellulose.